The IgLON Family Member Negr1 Promotes Neuronal Arborization Acting as Soluble Factor via FGFR2 - Pischedda, Francesca; Piccoli, Giovanni (Frontiers in Molecular Neuroscience, 2016)
IgLON proteins are GPI anchored adhesion molecules that control neurite outgrowth. In particular, Negr1 down-regulation negatively influences neuronal arborization in vitro and in vivo. In the present study, we found that the metalloprotease ADAM10 releases Negr1 from neuronal membrane. Ectodomain shedding influences several neuronal mechanisms, including survival, synaptogenesis and the formation of neurite trees. By combining morphological analysis and virus-mediated selective protein silencing in primary murine cortical neurons, we found that pharmacologically inhibition of ADAM10 results in an impairment of neurite tree maturation that can be rescued upon treatment with soluble Negr1. Furthermore, we report that released Negr1 influences neurite outgrowth in a P-ERK1/2 and FGFR2 dependent manner. Together our findings suggest a role for Negr1 in regulating neurite outgrowth through the modulation of FGFR2 signalling pathway. Given the physiological and pathological role of ADAM10, Negr1 and FGFR2, the regulation of Negr1 shedding may play a crucial role in sustaining brain function and development.